Odpowiedź :
Odpowiedź:
kontynuując równanie
[tex]3 {x}^{2} + 6x + 2 {x}^{2} + x - 8x - 4 = 5 {x}^{2} - x - 4[/tex]
[tex]10 {a}^{2} - 6a - 2 {a}^{2} - 8a - 3a - 12 = 8 {a}^{2} - 17a - 12[/tex]
[tex]6 {u}^{2} - 3u - 4u + 2 - 10 {u}^{2} - 15u = - 4 {u}^{2} - 22u + 2[/tex]
[tex]6 {y}^{2} + 9y - 10y - 15 - 15y + 6 {y}^{2} = 12 {y}^{2} - 16y - 15[/tex]
Odpowiedź:
[tex]x(3x+6)+(x-4)(2x+1)=3x^2+6x+2x^2+x-8x-4=5x^2-x-4\\\\\\2a(5a-3)-(2a+3)(a+4)=10a^2-6a-(2a^2+8a+3a+12)=\\\\=10a^2-6a-2a^2-8a-3a-12=8a^2-17a-12\\\\\\(3u-2)(2u-1)-5u(2u+3)=6u^2-3u-4u+2-10u^2-15u=-4u^2-22u+2\\\\\\(3y-5)(2y+3)-3y(5-2y)=6y^2+9y-10y-15-15y+6y^2=12y^2-16y-15[/tex]